National Consensus on the Assessment of Visual Function for Driving in Switzerland - Blaser, Frank; Schneebeli, Martina; Keller, Kristina H.; Pfäffli, Matthias; Todorova, Margarita G.; Kaeser, Pierre-François; Anastasi, Stefano; Wildberger, Hannes; Bochmann, Frank; Zweifel, Sandrine; Said, Sadiq (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose To establish a national consensus on assessing visual function for fitness to drive in Switzerland.Methods The minimum medical requirements for visual function for fitness to drive are regulated by Swiss Federal Law, namely, by the Traffic Licensing Ordinance (TLO). The medical examination techniques relevant in this context and their assessment are not further specified therein, which leads to legal inequality among drivers and uncertainty among examiners. We established a study group of representatives of the Traffic Medicine Section of the Swiss Society of Forensic Medicine and the Traffic Commission of the Swiss Society of Ophthalmology to develop a national consensus on assessing visual function for fitness to drive in Switzerland. In structured meetings, the authors discussed medical examination techniques and available international and local recommendations on this topic, with respect to Swiss legislation. In the event of a contrary opinion, the topic was discussed again in a follow-up session until we reached an agreement. We defined consensus as complete agreement on the subject under discussion.Results The study group held five in-person meetings between March 2019 and January 2023. The authors developed recommendations intended for all professional groups assessing driving fitness. We prepared an aid for daily practice on how to examine the minimum medical requirements for visual function listed in the TLO Annex 1, using standardized test procedures and considered how to interpret the findings obtained, accounting for aspects of traffic medicine and ophthalmology.Conclusions A consensus on the assessment of visual function for fitness to drive in Switzerland is crucial to ensure legal equality for drivers and legal certainty for examiners. Regular review of the consensus is imperative if we are to consider future legal developments and new scientific evidence in assessing fitness to drive.
Keywords: fitness to drive; perimetry; consensus; traffic licensing ordinance; visual function